2021
DOI: 10.3390/cancers13174349
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Tumor Heterogeneity Revealed by Mass Spectrometry Imaging Is Associated with the Prognosis of Breast Cancer

Abstract: Intra-tumor heterogeneity (ITH) results from the coexistence of genetically distinct cancer cell (sub)populations, their phenotypic plasticity, and the presence of heterotypic components of the tumor microenvironment (TME). Here we addressed the potential association between phenotypic ITH revealed by mass spectrometry imaging (MSI) and the prognosis of breast cancer. Tissue specimens resected from 59 patients treated radically due to the locally advanced HER2-positive invasive ductal carcinoma were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…We have previously found that a higher level of intratumor heterogeneity addressed by MALDI-MSI was associated with better outcomes in patients with HER2-positive breast cancers. Moreover, increased heterogeneity observed in that study was associated with the presence of tumor-infiltrating lymphocytes, which prompted us to hypothesize that a more favorable prognosis of breast cancer patients who had a higher level of ITH revealed by MALDI-MSI was associated with a higher level of immune cells enhancing the response to treatment [ 21 ]. We found here that continuous/dense pattern of lymphocyte infiltration at the tumor/host interface correlated with a higher level of phenotypic ITH, which suggested similar mechanisms in patients with locally advanced oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously found that a higher level of intratumor heterogeneity addressed by MALDI-MSI was associated with better outcomes in patients with HER2-positive breast cancers. Moreover, increased heterogeneity observed in that study was associated with the presence of tumor-infiltrating lymphocytes, which prompted us to hypothesize that a more favorable prognosis of breast cancer patients who had a higher level of ITH revealed by MALDI-MSI was associated with a higher level of immune cells enhancing the response to treatment [ 21 ]. We found here that continuous/dense pattern of lymphocyte infiltration at the tumor/host interface correlated with a higher level of phenotypic ITH, which suggested similar mechanisms in patients with locally advanced oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The acquired MSI spectra were preprocessed by computationally performed mass channels unification, baseline subtraction, outlying spectra identification, peak alignment, TIC normalization, and peak detection using Gaussian mixture modeling (GMM) of the average spectrum; the procedure of our spectra processing pipeline was described in detail elsewhere [ 21 , 41 ]. Abundance of a particular component was estimated by pairwise convolution of the GMM components and individual spectra.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A new method combining MALDI-MSI with IHC, termed MALDI-IHC, has been described, allowing the high-plex MSI of a wide range of biomarkers in various tissues, including BC [ 17 ]. In advanced HER2+ invasive ductal carcinoma, MALDI-MSI emphasized the association between intratumor heterogeneity and the prognosis of BC; the higher heterogeneity of tumors with a better prognosis reflects the presence of infiltrating immune cells that facilitate the treatment response [ 29 ]. An integrated experimental design based on IHC and histology-directed MSI defined the proteome profile of tumor microenvironment (TME), suggesting that the phosphatase and tensin homolog (PTEN) expression may be associated with different collagen types and regulation by PT sites of modification [ 30 ].…”
Section: Introductionmentioning
confidence: 99%